Treatment of Burning Mouth Syndrome Accompanied With Xerostomia and Dysgeusia in Diabetes Mellitus Patients - Raziv Ganesha; Ni Nyoman Gemini Sari; I Nyoman Gede Juwita Putra (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Burning mouth syndrome is pain in the oral mucosa with or without signs of or without specific signs of lesions. The manifestations of Diabetes in the oral cavity are xerostomia, dysgeusia and burning mouth syndrome. Purpose of this case report is to describe the management of Burning mouth syndrome cases accompanied by Xerostomia and Dysgeusia in patients with Diabetes. Case: A 65-year-old woman presented with complaints of pain felt was a burning sensation on the tongue. patient felt the burning pain during a day but also at night for the past 2 weeks. Case Treatment: The diagnosis in this case is Burning mouth syndrome accompanied by Xerostomia due to Diabetes. Patient was given oxyfresh® for 3x 10 ml and Becomzet® 1x1. The patient had DL, GDP (110), GD2PP (145), HbA1C (7.2), SGOT (27), and SGPT (29) and Sialometry (0.3ml). Patient accepted the treatment and followed the instructions given. Patient was healed on the third visit. Discussions: Burning mouth syndrome is a burning and uncomfortable or stinging feeling with a normal clinical feature. Xerostomia and Dysgeusia are often concurrent symptoms so it is called the triad symptom of burning mouth syndrome. Treatment with oxyfresh® which contains xylitol as an antimicrobial that reduces the risk of caries, zinc acetate which is effective in maintaining oral moisture and aloe is useful for reducing irritation, pain and inflammation so as to reduce pain in burning mouth syndrome. Conclusion: Treatment in this case was successful with good cooperation from the patient to accelerate healing.